PP26 Caesarean Delivery and Subsequent Birth Interval, Ectopic Pregnancy, Miscarriage or Stillbirth-a Danish Register-based Cohort Study. (10th September 2013) - O'Neill, S M; Agerbo, E; Kenny, L C; Henriksen, T B; Kearney, P M; Greene, R A; Mortensen, P B; Khashan, A S
Abstract : Background: Despite high caesarean delivery rates worldwide, limited data are available on the effect of a prior caesarean delivery on subsequent fertility. Aim: To estimate the time to next birth and the risk of miscarriage, ectopic pregnancy and stillbirth in women with a prior caesarean delivery compared to women with a prior vaginal delivery. Methods: Using Danish registry data we identified a cohort of women giving birth between 1982 and 2010 (n = 833, 162). The cohort was followed from the index birth until the next birth or censoring by death, emigration or study end (31/12/2010). Women with an index caesarean section were compared to women with an index vaginal birth by stratified Cox regression models using SAS version 9.2 Results: Women with an index caesarean were less likely to have a subsequent delivery and had an increased time to next birth (HR 0.83 [95% CI 0.82, 0.84]). Sub-group analyses by smoking status, history of fertility services, maternal BMI, preterm birth & low birth weight did not modify results. Analyses for ectopic pregnancy and miscarriage showed no increased HR among women with a prior caesarean section; however a significantly increased HR for subsequent stillbirth was reported (1.16 [1.04, 1.28]). Conclusion: Prior caesarean delivery, particularly elective and maternally requested caesareans were associated with an increased time to next birth. An increased hazard ratio of stillbirth in subsequent deliveries but not ectopic pregnancy or miscarriage among women with an index caesarean was also found.